2015
DOI: 10.1103/physrevb.92.180507
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity dichotomy in K-coated single and double unit cell FeSe films onSrTiO3

Abstract: We report the superconductivity evolution of one unit cell (1-UC) and 2-UC FeSe films on SrTiO 3 (001) substrates with potassium (K) adsorption. By in situ scanning tunneling spectroscopy measurement, we find that the superconductivity in 1-UC FeSe films is continuously suppressed with increasing K coverage, whereas non-superconducting 2-UC FeSe films become superconducting with a gap of ~17 meV or ~11 meV depending on whether the underlying 1-UC films are superconducting or not. This work explicitly reveals t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…However, it generates a pronounced in-gap bound state at + 4.5 mV (Fig. 3(g) The K atoms appear as single bright dots and contribute somehow charge transfer to monolayer FeSe films [29]. From the measured local density of states on surface K-atom, the superconductivity is basically undisturbed since most of our observation is consistent with previous results [20]: the coherence peaks remain almost unchanged and there is no in-gap bound state.…”
supporting
confidence: 90%
“…However, it generates a pronounced in-gap bound state at + 4.5 mV (Fig. 3(g) The K atoms appear as single bright dots and contribute somehow charge transfer to monolayer FeSe films [29]. From the measured local density of states on surface K-atom, the superconductivity is basically undisturbed since most of our observation is consistent with previous results [20]: the coherence peaks remain almost unchanged and there is no in-gap bound state.…”
supporting
confidence: 90%
“…Surprisingly, T c dramatically increases to ∼70K in 1ML FeSe/STO(001) [2]. Charge transfer from STO is widely believed to play an important role in the superconducting mechanism [3], which is supported by doping experiments of bulk or multilayer FeSe [4][5][6][7][8][9]. However, the T c in the doped FeSe systems is less than 50 K, which suggests that there are other substrate related effects contributing to the higher T c in 1ML FeSe/STO(001).…”
mentioning
confidence: 99%
“…However, at present, there are no experimental results that demonstrate the direct relation between the electron-phonon coupling and the enhancement of the superconductivity. Nevertheless, the interface superconductivity has also been found in related materials such as FeSe on BaTiO 3 [161], Te-doped FeSe on STO [162], KFe 2 Se 2 on STO [148], FeSe on STO(110) [163,164], and FeSe on anatase TiO 2 [165]. In addition, replica bands were also observed in monolayer FeSe on anatase TiO 2 [166].…”
Section: -System MLmentioning
confidence: 92%
“…They also found that the superconducting phase of 3-ML thick films is dome-shaped in a temperature-vs-doping-level phase diagram, suggesting an unconventional mechanism for the superconductivity. Subsequently, the K-adsorption effects were investigated in detail by other several research groups using ARPES [148,149] or STM/STS [150][151][152], and their common results were that the electron-doping can enhance the superconductivity even for a 50-ML-thick FeSe film [149] and the superconducting gap size of the doped samples becomes larger as the thickness becomes thinner, suggesting an interfacial effect for the enhancement of superconductivity in monolayer FeSe.…”
Section: -System MLmentioning
confidence: 99%